COROMINAS, JORDI, y VICENS, JOAN ALBERT, XAVIER ZUBIRI. La soledad sonora - Barroso Fernández, Óscar (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
(Taurus, Madrid, 2006). 920 pp.